Optimization of see do il extraction process parameters from Brucea javanica using Design of Experiment (DoE) - Hasni, K.; Ilham, Zul (IOP Publishing, 2019)
The project was done to improve Soxhlet process for extraction of oil for seeds of Brucea javanica and explore its various applications. The optimization was done by RSM (response surface methodology) using Box Behnken design of experiment (DoE). Properties of the Brucea javanica oil (BJO) was determined using Gas/Mass Spectrometric approach and Fourier Transform Infrared Spectroscopy (FT-IR) analysis. GCMS analysis indicated that important fatty acid are presence in BJO and FTIR suggested the presence of core functional groups in BJO. Quadratic model was used to analyse the results obtained from the optimised experimental design. ANOVA of developed model showed good presentation of model with R 2 value of 0.9078. Similarly, it was discovered that model were significant because their probability values (p-values) were discovered to be less than 0.05. The design of experiment showed a highest yield of 44.89 % at 75°C, 6hour extraction time and hexane 425ml.